Pharmacist Involvement in Population Health Management for a Pediatric Managed Medicaid Accountable Care Organization - Catherine Kuhn; Brigid K. Groves; Chester Kaczor; Sonya Sebastian; Ujjwal Ramtekkar; Joshua Nowack; Christina Toth; Olivia Valenti; Charitha Gowda (MDPI AG, 2019)
Accountable care organizations (ACOs) have emerged as an effective healthcare delivery model for managing quality and cost at a population level. Within ACOs, pharmacists are critical for the delivery of high-value health care, offering patients and health care providers medication-related training, resources, and guidance that can improve quality of care at lower costs. Partners For Kids (PFK), one of the oldest and largest pediatric ACOs in the country, has successfully leveraged pharmacists to provide population health management and medication management to promote health outcomes for individual patients and the overall population it serves. This review explores how the inclusion of pharmacists in the development and execution of various quality improvement initiatives within PFK has positively impacted outcomes for patients while also lowering overall spend. A catalog of interventions is provided to offer various ways that pharmacists can intersect as providers in the triad of patient/family, payor, and provider. By providing enhanced training and education, on-site guidance, medication management, and population-level data analysis, pharmacists are able to identify and improve inefficiencies in care. Moving forward, ongoing engagement of pharmacists in health care operations will be a necessary feature to maximize health care value.